Historical Account of Key Words in Non-Financial Report Titles: (A review of FT 500 corporations from 1989 to 2007) (Issues in Social and Environmental Accounting (ISEA), 2010)
This paper investigates the history of, and trends in, non-financial reporting, based on title analysis. The database consists of the titles of non-financial reports issued by FT 500 corporations from 1989 to 2007. The frequency and development of the three key words environment, sustainability and responsibility (coded as “environment”, “sustainab” and “responsib” to catch relevant versions) are investigated.  The key words were initially applied by a few companies, and then grew in popularity. While “sustainab” and “responsib” are still growing in popularity, “environment” grew, peaked around 2002 and then reduced in frequency as a term in the titles.  Based on business theories, the paper discusses alternative explanations for why corporations introduced the new key words in their non-financial reports. Whereas issuing non-financial reports can be understood from a legitimacy perspective, the introduction of new key words in the titles can be explained by a multitude of alternative theories.